Enteromyxum scophthalmi - Palenzuela, Oswaldo; Piazzon de Haro, María Carla; Sitjà-Bobadilla, Ariadna (5m Books, 2021)
Enteromyxum scophthalmi is the causative agent of a parasitic emaciative disease that affects turbot (Scopthalmus maximus), known as sunken-head syndrome or turbot enteromyxosis. This organism is a myxozoan, a group of microscopic endoparasites that resemble protozoans but which are in fact metazoans, related to free-living cnidarians. E. scophthalmi is akin to E. leei, a different species which causes similar syndromes in various fish species in the Mediterranean and worldwide (reviewed in Sitjà-Bobadilla and Palenzuela, 2012). E. scophthalmi develops in the intestinal epithelium of turbot, causing severe catarrhal enteritis and impairing intestinal function. The infection is usually lethal just a few weeks after infection. Although typical myxozoan life cycles usually alternate between a fish and an invertebrate host (annelids or bryozoans), Enteromyxum spp. are unique in their ability to be transmitted directly between fish. Thus, E. scophthalmi has been demonstrated to be experimentally transmissible to naïve turbot from infected fish through three routes: (1) cohabitation in the same tank; (2) receiving contaminated effluent water from tanks holding the infected fish; and (3) the oral route (Redondo et al., 2002, 2004). In aquaculture settings this transmission occurs readily and spontaneously, completely